Occupational therapy for children with DME or twice exceptionality : a practical approach to support high learning potential, sensory processing differences and self-regulation - Ferreira, Mariza; Howell, Rebecca (Education consultant) (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Children with high learning potential or giftedness have remarkable potential. Despite this, these children can struggle to participate in everyday life because of a range of needs that are sometimes misunderstood, overlooked or not adequately addressed, leading to underachievement and in turn, low self-esteem. Needs that, in many cases, paediatric occupational therapists are best suited to address. The practical resource offered in the book, the DME-C approach, is a tried-and-tested approach to help children who have challenges relating to their high learning potential, as well as sensory processing differences, unhelpful thought patterns and self-regulation. It draws on the heart of occupational therapy that considers the whole profile of the child, actively caters to the unique profiles of children with DME or twice exceptionality (2e), and guides therapists towards therapy provision that is strengths-based and achieves favourable outcomes. This book includes a clear and comprehensive introduction to high learning potential and DME or twice exceptionality (2e), along with guidance to help identify children with these profiles. It covers questions and concerns occupational therapists may have when working with children with DME or 2e; considers the similarities and differences between high learning potential/DME/2e and neurodivergent conditions such as Developmental Coordination Disorder, Autism and ADHD; with a focus on sensory processing differences; explains, in easy-to-understand language, the full DME-C therapy approach, with a range of example activities to use in therapy to achieve its principles, and a suggested therapy progression plan; is packed full of real-life case studies to translate theory into practice, and empowers therapists and educational professionals further by drawing attention to how they can better relate to children with DME/2e in therapy regardless of the children's specific needs. With the voices of parents and children at its heart and full of examples, this resource is essential reading for occupational therapists, SENCOs, education psychologists and other relevant professionals, who want to improve the lives and wellbeing of children with DME or twice exceptionality and help them reach their full potential"--
"A Speechmark book" -- cover.
Keywords: Occupational therapy for children; Twice-exceptional children -- Rehabilitation; Twice-exceptional children -- Education; EDUCATION / General; EDUCATION / Special Education / General; EDUCATION / Special Education / Gifted